Ask Question
5 November, 09:33

F (1) = 2x^3 - 3x^2 + 7

0
Answers (2)
  1. 5 November, 10:20
    0
    f = 2x^3 - 3x^2 + 7
  2. 5 November, 10:40
    0
    f (-1) = 2x3-3x2+7.

    Step-by-step explanation:

    Step 1:

    Equation at the end of step 1:

    -f - (((2 • (x3)) - 3x2) + 7) = 0

    Step 2:

    Equation at the end of step 2:

    -f - ((2x3 - 3x2) + 7) = 0

    Pull out like factors:

    -f - 2x3 + 3x2 - 7 =

    -1 • (f + 2x3 - 3x2 + 7)

    f + 2x3 - 3x2 + 7 is not a perfect cube

    -f - 2x3 + 3x2 - 7 = 0
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “F (1) = 2x^3 - 3x^2 + 7 ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers